System Shift Risk, Human Capital, and Organizational Culture: A Proxy-Based Exploratory Validation with Methodological Safeguards - Raymond Rubianto Tjandrawinata (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
This study examines whether the System Shift Framework can explain variation in organizational culture, human capital readiness, and resistance to adaptive change. Using a proxy-based firm-level dataset of 889 organizations, the analysis operationalizes seven System Shift dimensions: System Condition (SC), Domain Lock (DL), Actor Complexity (AC), Chokepoint Pressure (CP), Position Quality (POS), Strategy Quality (STR), and Feedback Maturity (FB). The composite risk index is calculated as SC + DL + AC + CP ? POS ? STR ? FB, where higher values indicate stronger cultural and systemic resistance to adaptive transformation. The analysis evaluates associations with Culture Effectiveness, Norms Alignment, Values-Norms Gap, Innovation Performance, Productivity Performance, Compliance and Ethics Performance, and System Shift Success. Results show that the System Shift Risk Score is strongly and negatively associated with Culture Effectiveness (r ? ?0.920), Norms Alignment (r ? ?0.979), and Compliance and Ethics Performance (r ? ?0.761). Regression models explain substantial variance in culture-proximal outcomes, particularly Norms Alignment and Compliance and Ethics Performance, while explanatory power is more modest for innovation and productivity outcomes. Classification analysis shows that logistic regression provides more stable discrimination than random forest under conditions of strong class imbalance, with approximately 2.6% of firms classified as System Shift Success cases. Random forest feature importance identifies Strategy Quality as the dominant predictor of System Shift Success, followed by chokepoint pressure, internal position, and system condition. Cluster analysis identifies three interpretable states: shift-ready and adaptive culture, transitional and mixed condition, and high-risk and resistant culture.